Vivarium Darmstadt (Karakul Circulations: Colonial Economies and the Un_Making of Disciplinary Knowledges in Germany and Namibia, 2020)
97 JPEG files of a visit to a Karakul enclosure in a zoo in Germany
Keywords: Karakul sheep; Breeding; Zoo animals; Postcolonialism; South Africa; Agriculture; Colonisation; Germany; Namibia; Swakara; Karakul Circulations; Colonial Economies; Karakul Farming; Colonial South-West Africa; German Colonialism; Karakul Sheep Industry